Using mismatch negativity to study central auditory processing in developmental language and literacy impairments where are we, and where should we be going? [article]. - Bishop, D. V. M.
A popular theoretical account of developmental language and literacy disorders implicates poor auditory temporal processing in their etiology, but evidence from studies using behavioral measures has yielded inconsistent results. The mismatch negativity (MMN) component of the auditory event-related potential has been recommended as an alternative, relatively objective, measure of the brain's ability to discriminate sounds that is suitable for children with limited attention or motivation. A literature search revealed 26 studies of the MMN in individuals with dyslexia or specific language impairment and 4 studies of infants or children at familial risk of these disorders. Findings were highly inconsistent. Overall, attenuation of the MMN and atypical lateralization in the clinical group were most likely to be found in studies using rapidly presented stimuli, including nonverbal sounds. The MMN literature offers tentative support for the hypothesis that auditory temporal processing is impaired in language and literacy disorders, but the field is plagued by methodological inconsistencies, low reliability of measures, and low statistical power. The article concludes with recommendations for improving this state of affairs. -- (from the author)